An Ethnoscience Study of the Tempe-Making Process as a Source of Contextual Science Learning: A Case Study of The Aikmual Village - Shelliana Iqlima; Mahrus Mahrus; Fathoni Arif Pratama; Elvina Riyanto; Asma Nadia Laily (Indonesian Journal of Educational Innovation, 2026)
Contextual learning in science education (IPA) demands integration of real-world phenomena familiar to students. This study examines the ethnoscientific aspects embedded in the tempeh-making process as a contextual resource for science learning. A qualitative descriptive case study was conducted in Aikmual Village, Central Lombok, involving participatory observation, in-depth interviews with three experienced producers, and documentation. The findings reveal that the tempeh production process integrates key scientific concepts across biology, chemistry, and physics, particularly in fermentation, biochemical transformations, and heat transfer mechanisms. Eight production stages were systematically mapped to relevant science competencies at the junior and senior high school levels. The study concludes that traditional tempeh-making practices have strong potential as ethnoscience-based learning resources to enhance students’ scientific literacy and contextual understanding, in line with the Merdeka Belajar curriculum.